Local placement test retrofit and building language assessment literacy with teacher stakeholders: A case study from Colombia. (July 2022) - Janssen, Gerriet
This article provides a single, common-case study of a test retrofit project at one Colombian university. It reports on how the test retrofit project was carried out and describes the different areas of language assessment literacy the project afforded local teacher stakeholders. This project was successful in that it modified the test constructs and item types, while drawing stronger connections between the curriculum and the placement instrument. It also established a conceptual framework for the test and produced a more robust test form, psychometrically. The project intersected with different social forces, which impacted the project's outcome in various ways. The project also illustrates how test retrofit provided local teachers with opportunities for language assessment literacy and with evidence-based knowledge about their students' language proficiency. The study concludes that local assessment projects have the capacity to benefit local teachers, especially in terms of increased language assessment literacy. Intrinsic to a project's sustainability are long-term financial commitment and institutionally established dedicated time, assigned to teacher participants. The study also concludes that project leadership requires both assessment and political skill sets, to conduct defensible research while compelling institutions to see the potential benefits of an ongoing test development or retrofit project.